Supramolecular intermediates in thermo-mechanochemical direct amidations - Stolar, Tomislav; Alić, Jasna; Talajić, Gregor; Cindro, Nikola; Rubčić, Mirta; Molčanov, Krešimir; Užarević, Krunoslav; Hernández, José G. (Chemical Communications, 2023)
We present a solvent-free thermo-mechanochemical approach for the direct coupling of carboxylic acids and amines, which avoids activators and additives. Non-covalent interactions between the reagents guide the formation of the amide bond.